Parenthood in Crisis 2.0: Motherhood in the Tension Between Homeschooling and Home Office: A Comparison After 1 Year of the Pandemic - Lange, Bianca; Ohlbrecht, Heike (International Dialogues on Education Journal, 2022)
The contact restrictions and closures of schools and childcare facilities in Germany in the course of the Covid 19 pandemic have presented families and parents with new challenges that have been accompanied by different (health) burdens and reinforce already existing gender differences in the division of tasks in families, especially with regard to care work. Women and mothers show themselves to be more burdened in the various dimensions of health in the course of the pandemic than men and fathers. In particular, the psychosocial dimensions of subjective health, especially the general experience of strain, stress, exhaustion and anxiety, increased again among women and mothers in the second lockdown. Reasons can be seen in a reinforcement of the unequal distribution of care work that already existed before the pandemic, as well as in a stronger mental load among women and mothers.